Asian foreign direct investments in the Visegrad countries: What are their motivations for coming indirectly? - Andrea S. Gubik; Magdolna Sass; Ágnes Szunomár (DANUBE: Law, Economics and Social Issues Review, 2020)
Asian foreign direct investments are significant in the Visegrad countries (Czech Republic, Hungary, Poland and Slovakia). Statistics compiled by the OECD's new balance of payments manual (BPM6) show that the FDI stock of Asian investors is significantly higher than the data on direct investors suggest, meaning that companies go through intermediary countries before the investment reaches its final destination. The purpose of the article is to analyse why Asian FDI invest through intermediaries rather than directly. The paper analyses the main reasons for this 'indirectedness' based on statistical data, other sources and semi-structured interviews with automotive and electronics companies. Our results show that the motivations for using an intermediary country can be manifold. Tax optimisation is often the reason why a company goes through a country with a more favourable regulatory environment. In addition, the geographical distance and global production chain considerations can be important, as well as the aim of companies from emerging countries to conceal the investor's real origin. The increasing number of acquisitions further enhances the share of indirect investments, as with the acquisition of a foreign parent company the new owner also inherits its subsidiaries.
Keywords: 330; Foreign Direct Investments; Asian Multinational Companies; Ultimate Investing Country; Visegrad Countries